An Analysis of Customer Satisfaction in Ambon City Water Supply Company - Jamaluddin, Jamaluddin; Baharuddin, Baharuddin; Zainal, Henni; Farwita, Syurwana; Yusriadi, Yusriadi (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2020)
Currently, the Water Supply Company of Ambon City has a very important role to provide drinking water services for a sustainable community by prioritizing customer satisfaction, increasing the company's contribution to Regional Original Revenue, increasing the professionalism of human resources and preserving air resources. The purpose of this study is to analyze customer satisfaction in the Ambon City Water Supply Company (PDAM). This research uses descriptive qualitative. The population in this study were all customers of the Ambon City Water Supply Company which is 9000 customers. Sampling incendentile technique used for the customers who receive the service which is 97 people. Data collection techniques in this study were interviews, observation and literature study. The analysis (design) technique that will be carried out describes the research variables examining customer satisfaction indicators, which of course using tabulation namely frequency tabulation of respondents 'answers to research questions, then a evaluation of percentages (%) is carried out to find answers to respondents' questions. The result of the study shows that the variables of reliability, responsiveness, assurance, and empathy are very satisfying.